CORRELATION OF INTERESTS WITH CAREER MOTIVATION CONTINUE YOUR STUDIES TO HIGHER COLLEGE REVIEWED FROM MODERN TEACHING - AZIZ NURI SATRIYAWAN; Luthfi Kamilia (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2024)
Efforts to create superior and competitive Human Resources are through an education process. This research aims to, among other things, the correlation berween interests and career motivation to continue studying at higher education for new students of PGMI STIT Muhammadiyah Tempurrejo Ngawi for the 2023/2024 Academic Year. The variables in the research are study interest and career motivation. The research method uses quantitative correlation research with data collection using questionnaires in the form of questionnaires via Google Form. The sample for this research consisted of 25 first semester students. The data analysis technique is simple linear regression with Prerequisite Test and Hypothesis Test. The results of the research show that there is a significant relationship between variables Continuing studies has various benefits, including the opportunity to get the right position and being able to increase confidence and abilities in certain scientific fields in the world of work and also as personal development itself as well as several benefits in implementing modern teaching, being able to recognize the potential of students, learning that focuses on students students where the presentation of material is project-based as an output from the Independent Curriculum.Keywords: Study Interests, Career motivation, Modern Teaching